Passive higher order mode filter for 850 nm multimode fiber transmission. Issue 8 (August 2017) - Chorchos, L.; Turkiewicz, J. P.; Szostkiewicz, L.; Napierala, M.; Ostrowski, L.; Bienkowska, B.; Nasilowski, T.
Abstract: We propose and evaluate performance of the higher order mode filter for 850 nm multimode fiber transmission. The developed passive component reduces impact of mode dispersion on the systems performance. Excellent operation in the 850 nm transmission experiments is shown.